Enhanced Thermal Properties of Composite Phase Change Material by Polydopamine-Driven Cu Nanoparticles - Peng Liu; Dongji Wu; Teng Xiong; Xi Cao; Zhonghui Tan; Wenye Lin; Ming Gao; Osman Gencel; Amin Shahsavar; Ahmet Sari; Xiaobin Gu (Energy Material Advances, 2025)
Paraffin wax (PW) is a typical organic phase change material (PCM) with superior thermal storage performance. However, its poor thermal conductivity, liquid leakage, and inadequate solar absorption have limited its commercial application in thermal management and solar energy utilization. To address these limitations, polydopamine (PDA) was first employed to modify diatomite (DT) to enable uniform deposition of metal Cu nanoparticles on its surface to construct as a DT/PDA/Cu supporting material. Then, the obtained supporting material was used to encapsulate PCM, and the prepared shape-stabilized PCM (SSPCM) with 50 wt.% PW exhibited no leakage, a prominent solar–thermal conversion ability, and a high thermal conductivity. The PW/DT/PDA/Cu SSPCM demonstrated a thermal conductivity of 1.115 W·m−1·K−1, which was up to 3.83 times larger than that of pure PW, and a pronounced photothermal conversion efficiency of 88.27%. The substantial performance enhancement can be attributed to the PDA modification-driven strong in situ and uniform deposition of Cu nanoparticles on the surface of DT. Furthermore, the SSPCM was also capable of generating a steady current of 39.3 mA. The study results provide an efficient method for the multiple energy conversion application of SSPCMs.